História e direito no constitucionalismo latinoamericano: o estado de coisas inconstitucional - Almeida, Antônio Ítalo Hardman Vasconcelos (2018)
The subject of this thesis is the legal concept of the unconstitutional State of Affairs (also said “of things”) as well as its Latin American roots. The investigation and analysis taken here were under interdisciplinary parameters commonly found in Legal History, using Wolkmer’s studies as a theoretical framework. In the context, it analyzes the unconstitutional state of affairs according to the bigger picture of New Andean constitutionalism or New Latin American constitutionalism, which is viewed as a set of practices and historical values that provided a progressive movement of right expansion in Latin America. It proposes the following problems for analysis: is the Unconstitutional State of Affairs an arising instrument from New Andean constitutionalism? For that, the hypothesis is shaped through a historical and comparative study of the constitutions of Colombia in 1991 and Brazil in 1988 as examples of a new modus of right proposition, creation, and law enforcement. Most importantly, the legal concept in discussion here gives room to a more robust protection of rights in the region.